Evaluasi Kepuasan Pelanggan Dalam Berbelanja Online Pada Aplikasi Shopee Menggunakan Metode Importance Performance Analysis - Anisa, Ayu; Saptari, Mochamad Ari; Fachrurrazi, Sayed (Bulletin of Computer Science Research, 2025)
Shopee is one of the most popular e-commerce platforms in Indonesia, especially among university students. At Malikussaleh University, it has become the preferred application for meeting both academic and personal needs. However, despite its high usage, there are still complaints regarding unsatisfactory service quality, such as delayed deliveries, difficulty in processing returns, and slow customer support responses. This study aims to analyze customer satisfaction with Shopee services using the Importance Performance Analysis (IPA) method to assess the alignment between service importance and performance. The study evaluates four key dimensions: Web Design, Fulfillment, Customer Service, and Security/Privacy. The results show that the average conformity level (TKI) across 17 service attributes is 94.59%. A TKI value below 100% suggests that the provided services have not fully met customer expectations. Moreover, the IPA quadrant analysis reveals that several attributes—such as delivery punctuality, responsiveness to complaints, and clarity of product information—fall into Quadrant A. Attributes in this quadrant are critical and underperforming, indicating top priorities for immediate improvement to enhance overall service quality.